Implications of the New American College of Cardiology Guidelines for Hypertension Prevalence in India - Venkateshmurthy, Nikhil Srinivasapura (JAMA Intern Med, 2018)
This study analyzes whether the lowered blood pressure threshold for hypertension in the 2017 American College of Cardiology/American Heart Association guidelines vs the JNC7 guidelines are associated with diagnosis prevalence of hypertension among adults in India.